2021
DOI: 10.1080/14702541.2021.1922738
|View full text |Cite
|
Sign up to set email alerts
|

Surging glaciers in Scotland

Abstract: Glacier surges are cyclic oscillations of velocity and mass resulting from internal dynamic instabilities. For surge-type glaciers, cycles of advance and retreat are decoupled from climate forcing, so it is important to consider the possibility that former glaciers may have been surge-type when making climatic inferences from their dimensions and chronologies. In this paper, climatic and glacier geometric data are used to show that Scotland was likely the location of a surge cluster during the Loch Lomond Stad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 142 publications
(243 reference statements)
0
9
0
Order By: Relevance
“…Finally, a 14 C‐dated stratigraphic section at Croftamie, near the terminus of the former Loch Lomond glacier, is widely cited as robust evidence for the LLR culminating late in the YD (Benn, 2021; Lowe et al., 2019; Macleod et al., 2011). This interpretation assumes that the overlying “Gartocharn till” was deposited as lodgement till by the advancing glacier (Coope & Rose, 2008; Rose, 1981; Rose et al., 1988), in which case the ten 14 C dates on underlying plant remains afford a maximum‐limiting age for the advance (Macleod et al., 2011; Rose et al., 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a 14 C‐dated stratigraphic section at Croftamie, near the terminus of the former Loch Lomond glacier, is widely cited as robust evidence for the LLR culminating late in the YD (Benn, 2021; Lowe et al., 2019; Macleod et al., 2011). This interpretation assumes that the overlying “Gartocharn till” was deposited as lodgement till by the advancing glacier (Coope & Rose, 2008; Rose, 1981; Rose et al., 1988), in which case the ten 14 C dates on underlying plant remains afford a maximum‐limiting age for the advance (Macleod et al., 2011; Rose et al., 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Ankerstjerne et al, 2015; Aradóttir et al, n.d. ; Benn, 2021; Darvill et al, 2017; Delaney et al, 2018; Evans et al, 2016; Lamsters et al, 2021; Sutherland et al, 2019, in review). CSR networks occur in submarginal to subglacial landform assemblages of the terrestrial surging‐glacier landsystem, with flutes, hummocks, pitted outwash and zig‐zag eskers (Evans et al, 2007, 2016; Evans & Rea, 1999, 2003; Schomacker et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the geomorphological evidence, it can only be concluded that, when surging, the Uisu glacier did not form any glacial landforms in its present-day forefield. It can also be expected that in the future, after the ice has completely melted in the terminal area with the supraglacial cover, the current extent of the Uisu glacier will be revealed by the spread of the hummocky moraine and by other glacial landforms formed in this zone (Benn 2021), if the latter are not buried or washed out during deglaciation. Therefore, the presence of hummocky moraine in the glaciated areas in the past and, at the same time, the lack of marginal glacial landforms, may indicate not only the long-term stagnation of the glacial terminal zone, but also a past surge.…”
Section: Discussionmentioning
confidence: 99%
“…Serrano & Martín-Moreno 2018). The maximum extents of some Pleistocene glacier lobes and glaciers in the mountains of North America and Europe could also have been associated with surging (Evans & Rea 1999;Benn 2021).…”
mentioning
confidence: 99%